Poverty persistence among Belgian elderly: true or spurious? - Marjan Maes (University of Essex, Institute for Social and Economic Research (ISER), 2008)
Based upon a longitudinal administrative dataset merged with the Socio-economic Survey of 2001 and the National Register, the majority of the poor elderly in Belgium appear to be persistently poor. The simultaneous estimation of a multiple, spell discrete, time hazard model shows that dependence in poverty is a true phenomenon. It also shows that besides observable characteristics that reduce poverty exit and increase re-entry there are, in addition, unobserved effects that lead to the same kind of poverty persistence. Controlling for unobserved effects and an initial condition problem significantly improved the fit of the model.
Keywords: 330